2022
DOI: 10.1016/j.marpol.2022.104954
|View full text |Cite
|
Sign up to set email alerts
|

Local practices and production confer resilience to rural Pacific food systems during the COVID-19 pandemic

Abstract: Resilience of food systems is key to ensuring food security through crisis. The COVID-19 pandemic presents an unprecedented shock that reveals varying levels of resilience of increasingly interconnected food systems across the globe. We contribute to the ongoing debate about whether increased connectivity reduces or enhances resilience in the context of rural Pacific food systems, while examining how communities have adapted to the global shocks associated with the pandemic to ensure food security. We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 67 publications
2
17
0
Order By: Relevance
“…In Indonesia, marine catches reported a rapid decline of fishing effort, traders, and fish prices, but many fishers returned, caught more fish, and maintained their incomes [4] . The degree of reliance on local versus imported food and sharing among households influenced the social resilience to curfews in Pacific fisheries [11] , [2] . Some artisanal fisheries in Africa showed low compliance to government curfews and high crowding at local landing sites (Okyere et al 2021; [12] ).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, marine catches reported a rapid decline of fishing effort, traders, and fish prices, but many fishers returned, caught more fish, and maintained their incomes [4] . The degree of reliance on local versus imported food and sharing among households influenced the social resilience to curfews in Pacific fisheries [11] , [2] . Some artisanal fisheries in Africa showed low compliance to government curfews and high crowding at local landing sites (Okyere et al 2021; [12] ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be a missed opportunity to actively promote an emerging business model built on new technologies and forms of social engagement that strengthen social and solidarity networks. These additional economic models could provide redundancy in the system and provide local independence from global systems in the face of potential future disruptions to global markets, as has been observed in other studies (Ferguson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 77%
“…We used the RAD framework to better understand the extent to which fishery adaptations to social changes stemming from COVID‐19 might represent an opportunity to either prevent or guide system transformation following an unprecedented SES social disturbance. Facilitating such adaptations may become increasingly necessary if large‐scale social disturbances become more common, as has been suggested is likely under current climate trajectories (Buma & Schultz, 2020 ; Ferguson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fishers are already accustomed to threemonth gaps in fishing, given the Seychelles' monsoon patterns. As such, the impacts of COVID-19 on fishers in island nations such as Seychelles may have been relatively minimal (Ferguson et al, 2022), and we observed several responses to this question that were more representative of all the changes fishers have had to make because of previous events over the past 20-30 years. We therefore stress the importance of critically evaluating survey questions and responses via pilot studies and making adaptive changes in survey phrasing and delivery to better capture targeted information.…”
Section: Discussionmentioning
confidence: 90%